THE CORRELATION OF QUALITY OF ANTENATAL CARE, MATERNAL COVID, AND MATERNAL MORTALITY DURING THE PANDEMIC PERIOD IN EAST JAVA, INDONESIA - Satyawan, Dandy Candra; Setyaningsih, Wahyu; Supangat, Ririn Widyowati; Ernawaty; Wulandari, Ratna Dwi (Universitas Airlangga, 2023)
Introduction: Indonesia's maternal mortality rate is still above the target of the Sustainable Development Goals (SDGs). Meanwhile, the trend of maternal mortality in Indonesia during the COVID- 19 pandemic in 2021 increased sharply from 4,627 to 6,865 cases in 2021. Aims: This study was conducted to analyze the relationship between the quality of maternal health services on the incidence of maternal COVID and maternal mortality during the COVID pandemic in East Java, Indonesia. Methods: The research was conducted in East Java Province in 2021. The sample was randomly selected as many as 35 samples from a total of 38 samples of Regencies / Cities. The data used secondary data sourced from data from the East Java Health Office. Data analysis used Person Correlation analysis with Chi-Square analysis method. Results: The first hypothesis did not find a relationship between quality of Antenatal Care services and Maternal COVID cases (p- value: 0.195, r: -0.087). The second hypothesis has a significant relationship between the Maternal COVID and the Maternal Mortality (p- value: 0.040, r: 0.548). Also, the third hypothesis showed a substantial correlation between Maternal Mortality and quality of Antenatal Care (p- value: 0.001, r: -0.555). Conclusion: There is a strong relationship between the high Maternal COVID cases and the quality of access to antenatal care services to the high Maternal COVID cases during the pandemic. There needs to be a strategy to improve the quality and access of antenatal care services in reducing the high maternal mortality rate.